Choeradoplana crassiphalla sp. nov. (Platyhelminthes: Tricladida: Geoplanidae): A new species of land planarian from the Atlantic Forest of Argentina - Negrete, Lisandro Hector Luis (2012)
A new species of land planarian from northeastern Argentina, Choeradoplana crassiphalla sp. nov., is described. This is the first report of Choeradoplana in the Atlantic Forest of Argentina and the second species of the genus for this country. Choeradoplana includes nine species of Neotropical land planarians. The new species is light brown with a thin clearer median stripe. The pharynx is bell-shaped. The copulatory apparatus presents a short and very high and thick penis papilla. Choeradoplana crassiphalla is compared with other species of the genus, especially with Ch. marthae, due to the similarity of the copulatory apparatus.